Studi Deskriptif Kualitatif tentang Partisipasi Remaja dalam Keikutsertaan Posyandu Remaja - Hilda Prajayanti; Maslikhah Maslikah (Jurnal Kebidanan Harapan Ibu Pekalongan, 2021)
Adolescence is a period of storm and stress, because adolescents experience many challenges both from themselves (biopsychosocial factors) and the environment (environmental factors). The complexity of health problems in adolescents, of course, requires a comprehensive and integrated treatment that involves all elements from across programs and related sectors. The establishment of the Youth Posyandu is expected to be a forum to facilitate adolescents in understanding adolescent health problems. Data collection uses primary data and secondary data. The instrument used in the form of interviews. The purpose of this study was to determine the description of youth participation in the participation of the Youth Posyandu. This study uses a qualitative descriptive research design with a case study approach, data collection uses primary data and secondary data. The data collection technique used in-depth interviews. The research instrument used an interview guide. The research subjects consisted of the main informants, namely teenagers who attended the youth posyandu as many as 5 people. The triangulation informants were 2 cadres and 1 health worker. The sampling technique used purposive sampling The data were analyzed using Content Analysis. The results showed that the youth posyandu activities included examination of TB, BB, TD, LILA and counseling on reproductive health. Factors that influence the participation of youth posyandu are by encouraging the cadres, the availability of facilities for the implementation of youth posyandu.